Konsep Masyiatullah dalam Proses Pendidikan Islam - Shalahudin Ismail; Ma’mun Zahrudin; Andewi Suhartini (Ta'allum: Jurnal Pendidikan Islam, 2020)
The purpose of this study was determining the ‘masyiatullah’ concept in Islamic education process. The approach in this study used a qualitative approach, an approach in natural objects condition, where researchers become key instruments. The results showed that masyiatullah concept was the core of Islamic education, where the concept become a solid foundation to form students who believe and have faith. Ideally, Islamic education theology can produce a generation who had the awareness that they are servants of God.